Implementasi Knowledge Management pada KLPM-PTS: Pembentukan Sharing Culture antar Anggota KLPM-PTS di Indonesia - Maryani Maryani (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This paper is an idea to implement a knowledge management system for a real action for optimization efforts of private higher institutions due to the development of national human resources. Knowledge management is a technique of organizing knowledge within an organization. The goal is to accelerate the innovation by improving the effectiveness and efficiency of knowledge absorption through knowledge sharing process. Four activities underlying knowledge management system are using knowledge, finding knowledge, creating knowledge and packaging knowledge. These processes required to convert tacit knowledge into explicit knowledge that can be transferred to other people. Regarding to the background of the Consortium members who come from all corners of the archipelago, a web based knowledge management system is the best option. The system is built on many aspects, but can do a variety of simplifications that can be realized in the form of knowledge management portal. To make this system developed well, some attitudes need to be cultivated to create, capture, capture, store, process and disseminate knowledge.